From Innovation to Pandora’s Box: Examining the Laws on Public Health Threats Emanating from Cloud Seeding - Paul Atagamen Aidonojie; Esther Chetachukwu Aidonojie; Hassan Ismaila Adebowale; Maria Edet Umo; Godswill Owoche Antai (Khazanah Hukum, 2025)
The global community is increasingly concerned about climate change and has explored various scientific methods, including cloud seeding, as temporary mitigation measures. Cloud seeding is a weather modification technique that induces precipitation by injecting clouds with chemical substances such as potassium iodide and silver iodide. While this method appears effective in addressing water scarcity and climate-related challenges, it poses severe threats to public health that have not been adequately addressed through legal frameworks. This study examines the effects of cloud seeding on public health and explores the necessity for legal intervention. The research adopts a qualitative methodology, utilizing content analysis of scientific literature, policy documents, and case studies from both primary and secondary sources. Data were scrutinized through descriptive and analytical methods and presented graphically to illustrate key findings. The study reveals that cloud seeding poses significant public health risks, including water contamination, skin cancer or irritation, respiratory disorders, and ecological imbalances. These health hazards stem from the chemical agents used in the seeding process and their potential accumulation in water sources and ecosystems. Furthermore, the research identifies a critical gap in global public health legislation, as no international laws directly regulate cloud seeding practices concerning public health and safety. The study concludes that while cloud seeding demonstrates potential as a climate change mitigation tool, public health and safety must be prioritized. It recommends establishing a comprehensive global regulatory framework to ensure safe practices, conducting rigorous health impact assessments before implementation, and maintaining public transparency in weather modification initiatives. These measures are essential to balance environmental benefits with the protection of human health and ecological integrity.